2020
DOI: 10.1515/scid-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of machine learning methods for predicting viral failure: a case study using electronic health record data

Abstract: BackgroundHuman immunodeficiency virus (HIV) viral failure occurs when antiretroviral therapy fails to suppress and sustain a person’s viral load count below 1,000 copies of viral ribonucleic acid per milliliter. For those newly diagnosed with HIV and living in a setting where healthcare resources are limited, such as a low- and middle-income country, the World Health Organization recommends viral load monitoring six months after initiation of antiretroviral treatment and yearly thereafter. Deviations from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…They found out that decision trees (C4.5) performed the best with model fitness and prediction accuracy of 84.45% and 74.21% respectively. These study findings were similar to studies conducted in Kenya (53) and China (54) that equally reported the decision trees prediction to perform better with an accuracy of 90% and 70.9% respectively. Noteworthy, the study from .…”
Section: Use Of Machine Learning In Healthcaresupporting
confidence: 90%
See 2 more Smart Citations
“…They found out that decision trees (C4.5) performed the best with model fitness and prediction accuracy of 84.45% and 74.21% respectively. These study findings were similar to studies conducted in Kenya (53) and China (54) that equally reported the decision trees prediction to perform better with an accuracy of 90% and 70.9% respectively. Noteworthy, the study from .…”
Section: Use Of Machine Learning In Healthcaresupporting
confidence: 90%
“…These results indicate that classification machine learning models can be used to map the different predictors to their respective classes. Likewise, these capabilities have been reported in similar rather challenging scenarios like predicting viral failure (53), tweets classification for disease surveillance (59), identification of HIV predictors for screening (60), and dermatology conditions (67). Therefore, this demonstrates the potential and applicability of machine learning algorithms to provide insights in scenarios where human decision-making would be limited.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These results indicate that classification machine learning models can be used to map the different predictors to their respective classes. Likewise, these capabilities have been reported in similar rather challenging scenarios like predicting viral failure [ 51 ], tweets classification for disease surveillance [ 43 ], identification of HIV predictors for screening [ 52 ], and cancer [ 53 ]. Therefore, this demonstrates the potential and applicability of machine learning algorithms to provide insights in scenarios where human decision-making would be limited.…”
Section: Discussionmentioning
confidence: 94%